Validation workshop on agriculture development domains in Nigeria - Adeogun, Grace (International Food Policy Research Institute, 2009)
In line with the Federal Ministry of Agriculture and Water Resources (FMAWR)’s vision of ensuring access, availability, and affordability of quality foods to all Nigerians and the objectives of the USAID Global Food Security Response Project of doubling agricultural productivity and removing constraints to movement of staple crops in Nigeria and beyond, the International Food Policy Research Institute (IFPRI) in collaboration with the FMAWR, USAID MARKETS program, and the International Institute of Tropical Agriculture (IITA) is in the process of identifying development domains for different crops across Nigeria’s agroecological zones as a step in updating Nigeria’s agricultural strategy. The workshop was designed as a technical exercise to solicit new information and to validate preliminary findings.